2017
DOI: 10.7150/ijms.19734
|View full text |Cite
|
Sign up to set email alerts
|

FUT2 genetic variants as predictors of tumor development with hepatocellular carcinoma

Abstract: Lewis antigens related to the ABO blood group are fucosylated oligosaccharides and are synthesized by specific glycosyltransferases (FUTs). FUTs are involved in various biological processes including cell adhesion and tumor progression. The fucosyltransferase-2 gene (FUT2) encodes alpha (1,2) fucosyltransferase, which is responsible for the addition of the alpha (1,2)-linkage of fucose to glycans. Aberrant fucosylation occurs frequently during the development and progression of hepatocellular carcinoma (HCC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Previously, Chambers et al reported that a synonymous variant (rs281377) and an intronic variant (rs516246) in FUT2 were associated with alkaline phosphatase (ALP) and γ-glutamyl transferase (GGT), respectively 4 . The coding rs1047781 variant has been reported to display a marginally significant association with an indicator of liver damage (AST/ALT ratio), but the association with absolute levels of AST or ALT is novel 39 . In mice, abrogation of Fut2 –/– function leads to acute liver damage and increased alkaline phosphatase, AST, and ALT levels 38 .…”
Section: Resultsmentioning
confidence: 98%
“…Previously, Chambers et al reported that a synonymous variant (rs281377) and an intronic variant (rs516246) in FUT2 were associated with alkaline phosphatase (ALP) and γ-glutamyl transferase (GGT), respectively 4 . The coding rs1047781 variant has been reported to display a marginally significant association with an indicator of liver damage (AST/ALT ratio), but the association with absolute levels of AST or ALT is novel 39 . In mice, abrogation of Fut2 –/– function leads to acute liver damage and increased alkaline phosphatase, AST, and ALT levels 38 .…”
Section: Resultsmentioning
confidence: 98%